Correcting the Count: Improving Vital Statistics Data Regarding Deaths Related to Obesity1. Issue 4 (15th November 2017) - McCleskey, Brandi C.; Davis, Gregory G.; Dye, Daniel W.
Abstract: Obesity can involve any organ system and compromise the overall health of an individual, including premature death. Despite the increased risk of death associated with being obese, obesity itself is infrequently indicated on the death certificate. We performed an audit of our records to identify how often "obesity" was listed on the death certificate to determine how our practices affected national mortality data collection regarding obesity‐related mortality. During the span of nearly 25 years, 0.2% of deaths were attributed to or contributed by obesity. Over the course of 5 years, 96% of selected natural deaths were likely underreported as being associated with obesity. We present an algorithm for certifiers to use to determine whether obesity should be listed on the death certificate and guidelines for certifying cases in which this is appropriate. Use of this algorithm will improve vital statistics concerning the role of obesity in causing or contributing to death.